Upaya Restorative Justice di Tingkat Penyidikan Melalui Konstruksi Diskresi Bhabinkamtibmas Studi Polres Wonosobo - Mukti Arif Efendi; Linda Ikawati (Program Studi Ilmu Hukum Fakultas Syari'ah dan Hukum Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2023)
In the era of globalization, it is not only increasing speed and acceleration in the economic field, as well as technology. But furthermore that this can trigger the development of social culture and patterns of people's behavior to become increasingly individual. Not to mention the existence of social media which makes people not only understand what they want, but also what they don't want such as the consumptive lifestyle of influencers and the existence of flexing behavior which creates jealousy at the grassroots level. This certainly encourages negative behavior in order to realize what people dream of becoming a reality instantly. Of course this then triggers people to commit crimes such as theft, fraud and so on. However, as is basically the rule of society, sometimes the crimes committed are not serious crimes. This can then be implemented as a settlement outside of criminal justice by using procedural diversion carried out in the field by bhabinkamtibmas which is the smallest unit currently owned by law enforcers who have scope of work in sub-districts/villages. The method used in this study is an empirical legal research method that focuses on processing qualitative primary data in the form of field findings. The data analysis method used is qualitative which is conveyed through descriptive grammar.